Empowering women entrepreneurs through digital literacy: a participatory action research in rural East Java - Irwan Darmawan (Indonesian Journal of Applied Community Research, 2026)
Background: Women entrepreneurs in rural coastal East Java play a crucial economic role but face limited participation in digital markets due to low practical digital literacy. Objective: This program aimed to enhance digital skills, confidence, and agency of women micro-entrepreneurs through a participatory empowerment approach. Method: A participatory action-oriented model was implemented, including needs assessment, training, mentoring, and collaboration with local institutions and women’s groups. Results: The program engaged 38 participants, with over 70% improving digital literacy and adopting social media for business promotion, alongside a shift toward hybrid online–offline practices supported by peer learning and a local UMKM digital community. Implication: These findings suggest that community-based, mentoring-driven digital literacy programs are effective in fostering sustainable and inclusive rural entrepreneurship. Novelty: The study introduces an integrated model combining participatory training, sustained mentoring, and village-level institutional support as a scalable framework for women’s digital economic empowerment.